2023
DOI: 10.3390/agronomy13071846
|View full text |Cite
|
Sign up to set email alerts
|

Weed Identification in Maize Fields Based on Improved Swin-Unet

Abstract: The maize field environment is complex. Weeds and maize have similar colors and may overlap, and lighting and weather conditions vary. Thus, many methods for the automated differentiation of maize and weeds achieve poor segmentation or cannot be used in real time. In this paper, a weed recognition model based on improved Swin-Unet is proposed. The model first performs semantic segmentation of maize seedlings and uses the resulting mask to identify weeds. U-Net acts as the semantic segmentation framework, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Through field trials, they identified the most effective weeding knife for different field conditions, achieving an impressive 85.91% weed removal rate and a minimal 1.17% crop injury rate. Zhang et al (2023) [131,134] introduce an improved Swin-Unet model for precise weed recognition in maize fields, achieving remarkable results with a mean intersection over union of 92.75% and a mean pixel accuracy of 95.57%. The model's high inference speed of 15.1 FPS further enhances its significance for real-time, accurate crop and weed segmentation, aiding the development of intelligent agricultural equipment.…”
Section: Advancements In Machine Learning For Weed Detectionmentioning
confidence: 99%
“…Through field trials, they identified the most effective weeding knife for different field conditions, achieving an impressive 85.91% weed removal rate and a minimal 1.17% crop injury rate. Zhang et al (2023) [131,134] introduce an improved Swin-Unet model for precise weed recognition in maize fields, achieving remarkable results with a mean intersection over union of 92.75% and a mean pixel accuracy of 95.57%. The model's high inference speed of 15.1 FPS further enhances its significance for real-time, accurate crop and weed segmentation, aiding the development of intelligent agricultural equipment.…”
Section: Advancements In Machine Learning For Weed Detectionmentioning
confidence: 99%
“…It can effectively capture long-distance dependencies by computing the correlation between all positions within a sample. (Jiang et al, 2022;Reedha et al, 2022;Zhang et al, 2023a) have added SA to the network to apply it to crop and weed detection and segmentation tasks. However, SA possesses high computational complexity and does not address the inter-sample connection, which contradicts the original objective of designing a lightweight network in this paper.…”
Section: Dual Attention Blockmentioning
confidence: 99%
“…Janneh et al [60] proposed an improved deep convolutional neural network (DCNN) combined with a lightweight backbone, a multi-level feature re-weighted fusion module, and a convolutional weighted fusion decoder for efficient weed control in agriculture. Zhang et al [61] introduced an improved Swin-Unet model for weed recognition in maize fields. The model addresses challenges such as color similarity and overlapping between weeds and maize, as well as varying lighting and weather conditions.…”
Section: Deep Learning Modelsmentioning
confidence: 99%